Current status and challenges in ultrasound diagnosis and treatment of thyroid nodules in China - ZHOU Jianqiao, ZHANG Lu, XU Shangyan (Zhenduanxue lilun yu shijian)
Thyroid nodules (TNs) exhibit a high prevalence rate of 36.9% in China, with a marked preponderance in females over males, and regional variations observed. Ultrasonography (US), due to its non-invasiveness, convenience, and high sensitivity, has emerged as the primary diagnostic tool for TNs. In recent years, advancements in US diagnostic techniques have flourished, including the Thyroid Imaging Reporting and Data System (TIRADS), multimodal US, fine-needle aspiration (FNA) coupled with molecular testing, and artificial intelligence (AI). Notably, the 2020 edition of the Chinese-specific C-TIRADS system has improved diagnostic accuracy by tailoring to China's healthcare landscape. Multimodal US assessment, integrating various US techniques, has significantly enhanced diagnostic efficacy, reducing unnecessary biopsies. Molecular testing and AI-assisted diagnosis have further improved diagnostic precision; however, the generalization capabilities of AI models and their long-term clinical application efficacy remain to be validated. Ultrasound-guided interventional therapies occupy a pivotal position in TN management, including chemical ablation and thermal ablation techniques. Chemical ablation is primarily utilized for cystic-predominant nodules, whereas thermal ablation is suitable for both cystic-solid and solid nodules, with their combined application yielding optimal results. Although the application of thermal ablation in thyroid micropapillary carcinoma remains controversial, preliminary studies have demonstrated its efficacy and safety. Despite the remarkable progress in US technologies for TN diagnosis and treatment, challenges persist, including inconsistent diagnostic criteria, disparities in equipment and technical expertise across regions and hospitals, and the absence of large-scale studies on the long-term efficacy and safety of thermal ablation. Future directions encompass refining risk stratification systems, intensifying research on multimodal US assessment, enhancing the generalization capabilities of AI models, standardizing the application of molecular testing, exploring indications for ablation therapy, and establishing standardized efficacy assessments.